IMPACT OF SUSTAINABILITY PRINCIPLES ON COMPANY VALUE IN MINING COMPANIES WITH PROFITABILITY AS MODERATING VARIABLE - Frederico Siahainenia, S.
Mining industry has unique characteristics compared to other industries, such as its non-renewable nature and specific geographical locations. Mining companies must adopt sustainable business models to be accepted by society and operate as planned. This study examines the relationship between the application of sustainability principles and company value, moderated by profitability, in mining companies listed on the Indonesia Stock Exchange (IDX). Data processing is carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results of the study indicate that sustainability indicators from economic and environmental aspects have an impact on the value of mining companies, but not from the social aspect. Profitability can moderate the relationship between the application of sustainability principles in the environmental aspect. However, profitability cannot moderate the relationship between the application of sustainability principles in the economic and social aspects. These findings emphasize the importance of applying sustainability principles in enhancing company value.